Communicating Around Interculturality in Research and Education - Irvan Syahrizal (Journal of Teaching and Learning)
The book instructs readers on how to communicate interculturally and supports them in reflecting on how they can renegotiate and reconstruct knowledge, ideologies, and relationships around the notion of interculturality. Anchored in the author's original and thought-provoking perspectives on interculturality, this interdisciplinary and globally insightful book explores how communicating around such notions cannot exclude ideologism, language, and translation issues or problematizing voice and silence in research and education. Written in an original and stimulating way, relying on a variety of genres and writing styles to mimic the dynamism and flexibility of the ideas under review, the authors urge us to (un)voice, scrutinize, nurture and galvanize our ways of dealing with interculturality ourselves and together with others in academia. The book's very specific focus on communicating around interculturality (rather than 'doing' interculturality) is a new and important step towards observing, analyzing, talking about, and contributing to today's complex and fragmented world.